Návrh optimální organizační struktury občanského sdružení a motivace jeho členů - Horáková, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce se zabývá organizační strukturou občanského sdružení a navrhuje vhodnou motivaci jeho členů. Popisuje jednotlivé druhy organizačních struktur, základní pojmy z oblasti managementu a nejvýznamnější metody řízení a motivace lidí. Pojednává o rozdílném pojetí řízení a fungování v ziskovém a neziskovém faktoru.

The bachelor’s thesis investigates an organizational structure of an association of persons and proposes a suitable motivation of its members. This work describes various organizational structures, basic terms from area of management and most significant methods of management and motivation of people. It also discusses various forms of management and functionality of not-for-profit organisations.
The Proposal of Optimal Organizational Structure of an Association of Persons and The Motivation of Its Members
Keywords: Cíl; kompetenční model; motivace; nezisková organizace; občanské sdružení; organizační struktura; plán; řízení podle cílů; sociogram; stimulace; strategie (firemní strategie); zpětná vazba.; Objective; competence model; motivation; non-profit-making organization; association of persons; organizational structure; plan; management by objectives; sociogram; stimulation; strategy (company policy); feedback.